Usability and accessibility for people with disabilities in Malaysian Mosques - Niya, Mahsa Dabbagh (2015)
Malaysia to become seeks to become a fully developed country by 2020. Among nine central challenges demonstrated in the body of the “Vision 2020” is “the challenge of establishing a fully caring society” (WAWASAN 2020). It is to cater welfare of all people without any discrimination, not only economically, but also socially and emotionally. There are groups of people in the society which are marginalized from full participation and enjoyment of services provided due to the limitations existed in the built environments. According to the social definition of disability, people become disabled due to the barriers exist in their surrounding not because of their impairments or limited abilities. Along with developed societies overcoming such dysfunctional built environments has become under consideration in Malaysia as well to remove barriers and provide equal access of people with disabilities (PWDS) to all public services. Notwithstanding practical steps taken, there are still dissatisfactions from the members of public toward public buildings which cause restriction in PWDS daily life. Previous studies has also raised claims against inaccessibility of mosque buildings as well. In order to realization of a barrier-free built environment for a huge portion of Malaysia population, this research aimed to investigate accessibility and usability of Malaysian mosques for PWDS. Five most prominent mosques of the country were selected for the purpose of this study and a qualitative multiple case study was carried out to this end. The most recent revision of available Malaysian Standard of MS 1184:2014, “Universal Design and Accessibility in the Built Environment - Code of Practice”, became the reference in this study. A comprehensive evaluation checklist was constructed for the purpose of a systematic observation including 162 checkpoints under 22 items of accessibility. Altogether, 5394 points in all five study cases were measured in order to evaluate their accessibility level. The principal dimensions of an accessible mosque introduced by this study. They are access to building, horizontal circulation, vertical circulation, and toilet and wet areas. Moreover, the average accessibility of all mosques measured at 40%. Tuanku Mizan mosque was the most accessible mosque among all by 63% accessibility level while, National mosque by only 26% was the least. Putra mosque with 46%, Sultan Salahuddin mosque 35% and Wilayah mosque 32% were respectively between them. The most common accessibility barriers of mosque diagnosed in this study were individual shower room and toilet for ambulant people in toilet and wet area dimension, inappropriate lift, ramp, and stair in vertical circulation, Signage and graphic symbols, floor and wall surfaces, and doors in horizontal circulation and finally parking and path to building in the access to building group of principal dimension. It is also concluded that, Malaysian Standard of MS 1184:2014 dose not comprehensively address the requirements of PWDS in mosque buildings. The implementation of these findings will contribute to the process of development practically, socially as well as academically.